2017
DOI: 10.1177/0038038517726647
|View full text |Cite
|
Sign up to set email alerts
|

Materially Constituting a Sustainable Food Transition: The Case of Vegan Eating Practice

Abstract: Informed by several intellectual turns and sub-areas of sociology this article explores veganism as a practice and argues that its nascent social normalisation can be partly explained by specific modes of material work with food performed by vegan practitioners. Based primarily on interview data with UK-based vegans the research identifies four modes of material constitution – material substitution, new food exploration, food creativity and taste transition – which are of particular importance in strengthening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 32 publications
2
89
0
Order By: Relevance
“…The presence of the latter indicated that veganism may slowly become more visible in the mainstream culture. These findings suggested that vegans might represent some of the stereotypes and challenges indicated in the literature [27,33,35,[39][40][41][42], as commented on in the study about the vegan foodscape by Bertella [51]. This aspect will be presented in the next section, which turns to the investigation at the individual level.…”
Section: National Newspapermentioning
confidence: 71%
See 3 more Smart Citations
“…The presence of the latter indicated that veganism may slowly become more visible in the mainstream culture. These findings suggested that vegans might represent some of the stereotypes and challenges indicated in the literature [27,33,35,[39][40][41][42], as commented on in the study about the vegan foodscape by Bertella [51]. This aspect will be presented in the next section, which turns to the investigation at the individual level.…”
Section: National Newspapermentioning
confidence: 71%
“…Differently from Twine's study, the current study focused on the broader experiential aspects of food as experienced by vegans. Based on studies concerning ethical eating [28][29][30][31] and vegetarianism/veganism [32][33][34][35], this study viewed the vegan food experience as possibly leading not only to a sense of integrity, personal identity-construction, self-development, and meaningfulness as suggested by Twine [27], but also to sensuous gratification, enjoyment and conviviality, serenity, and elitism.…”
Section: Veganism As a Lifestyle Choice Relating To Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Meat alternatives are regarded as a help to people in transition, if they find it difficult in the beginning to radically abstain from all varieties of meat products. They make the vegan lifestyle seem less restrictive (Twine, 2018). Consequently, major local food companies, such as 'Nuteko', 'Skriveru majas saldejums', 'Spilva', 'Valmiermuiza', 'Terapija', etc.…”
Section: Introductionmentioning
confidence: 99%